Peranan Jasa Ekosistem dalam Perencanaan Kebijakan Publik di Perkotaan - Dea Chintantya; Maryono Maryono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Natural ecosystems have an important role in various aspects of human life, either directly or indirectly.However, natural ecosystems are often considered less valuable because the ecosystem services providedlargely public goods that do not have a clear market price. Currently, There are a serious threat to naturalecosystems, especially in urban areas caused by growth in both population size, consumption, and humanactivities. The assessment of environmental services is very important in the process of formulating publicpolicy in order to realize sustainable development because in previous studies it is known that theseenvironmental services contribute significantly to the welfare of the community. In this paper, several previousnational and international literature and research studies have been used to establish a theoretical frameworkfor the identification of ecosystem services in urban areas and their role in the process of urban dan publicpolicy planning. Identification of urban ecosystem services focuses on crops and trees on road corridors, urbanparks, urban forests, cultivated land or yard, water bodies (rivers and lakes), and wetlands.